Revisiting the Cygnus OB associations. Issue 2 (16th September 2021) - Quintana, Alexis L; Wright, Nicholas J
ABSTRACT: OB associations play an important role in Galactic evolution, though their origins and dynamics remain poorly studied, with only a small number of systems analysed in detail. In this paper, we revisit the existence and membership of the Cygnus OB associations. We find that of the historical OB associations only Cyg OB2 and OB3 stand out as real groups. We search for new OB stars using a combination of photometry, astrometry, evolutionary models, and an SED-fitting process, identifying 4680 probable OB stars with a reliability of >90 per cent. From this sample, we search for OB associations using a new and flexible clustering technique, identifying six new OB associations. Two of these are similar to the associations Cyg OB2 and OB3, though the others bear no relationship to any existing systems. We characterize the properties of the new associations, including their velocity dispersions and total stellar masses, all of which are consistent with typical values for OB associations. We search for evidence of expansion and find that all are expanding, albeit anisotropically, with stronger and more significant expansion in the direction of Galactic longitude. We also identify two large-scale (160 pc and 25 km s −1 ) kinematic expansion patterns across the Cygnus region, each including three of our new associations, and attribute this to the effects of feedback from a previous generation of stars. This work highlights the need to revisit the existence and membership of the historical OB associations, if they are to be used to study their properties and dynamics.